Effect of double-layer composite absorbing coating on shielding effectiveness of electromagnetic shielding fabric. (24th May 2019) - Duan, Jiajia; Wang, Xiuchen; Li, Yayun; Liu, Zhe
Abstract: In order to meet the demand for high-performance electromagnetic shielding fabrics, using absorbing coatings to improve the shielding effectiveness has become an research object increasingly. The effect of double-layer mixed material's absorbing coatings on electromagnetic shielding fabrics has not been clarified currently. At the same time, it is difficult to satisfy the broadband requirement for a single type of absorption layer. Carbon nanotubes, graphene, ferrite and nano-nickel powder are used in this paper. Which made it content at 15%, 25% and 35% respectively. The shielding effectiveness test of the stainless steel electromagnetic shielding fabric coating was carried out by the DR-SO4 electromagnetic shielding test system. Through the experiment, some findings are summarized as followed. Regardless of the same mixed materials, different content of shielding effectiveness comparison experiments, or the comparison of the performance of different kinds of materials mixed with the same content of screen combination, when the content is 15%, the best shielding effectiveness is the double-layer combination of Graphene + Ferrite and Graphene + Nickel. Which peak value is 68 dB respectively. In the analysis of the influence factors of the test coating, the larger the thickness and the corresponding resistance value smaller, the higher the combined shielding effect value. The optimal combination order of shielding effectiveness is: reflective layer + absorbing layer + absorbing layer + reflective layer. This paper revealed the influence of double-layer hybrid coating on the shielding effectiveness of electromagnetic shielding fabrics. It has important academic significance for the design, production and evaluation of high performance electromagnetic shielding fabrics.